Education strategy in a changing society : personalised, smarter, lifelong learning in the 21st century - Slattery, Martin (New York : Routledge, 2024)
"Placing the UK in a global context, this book engages with the emerging international debate on educational futures in the twenty-first century. It examines the post-pandemic paradigm shift in educational practice in countries around the world and presents international case studies of emerging future practice. It explores how the new curriculum models, new approaches to pedagogy, new educational technology such as AI and even robotics, might help to transform education, help "level-up" learning and help younger generations cope not only with the future as we know it but also the future that we don't. This book will appeal to policymakers, students and scholars interested in the sociology of education, education policy, international education, international development, and future studies, as well as those with a general interest in Education in the future. While it embraces the global context and the mega-forces therein, it is specifically focused on the challenges for English education today and the potential strategies for moving forward to the all-inclusive, personalized, smarter and lifelong learning needed for tomorrow"--
Introduction -- Part 1. The Crisis in Education Today -- Part 2. The Global Context & Challenges for Education Today -- Part 3. The Forces for Change in Education Today -- Part 4. A Framework & Strategy for Educational Change.
Keywords: Educational change -- Case studies; Educational leadership -- Case studies; Continuing education -- Effect of technological innovations on; Adult education -- Curricula -- Computer-assisted instruction; Distance education -- Computer network resources -- Social aspects; Open learning -- Social aspects; SOCIAL SCIENCE / Sociology / General